The problem of equity in the philosophy of the age of enlightenment in the context of growing of european states and the formation of civil society - Сабадуха, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
It is researched the evolution of equity issues in the European philosophy of the Age of Enlightenment. It`s analyzed the social andphilosophical aspects of equity in T. Hobbes, John. Locke, K. Helvetius, D. Diderot, D. Hume. It`s discovered the common and differencesin their views.